Ekspedisjonsfotografi i polare områder - Barr, Susan (Bildet lever! : bidrag til norsk fotohistorie. 7, 1999)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; fotografi; historie; polarekspedisjoner; polarområdene

The importance of charged aerosols in the polar mesosphere in connection with Noctilucent Clouds and Polar Mesosphere Summer Echoes - Blix, Tom Arild (The Antarctic and Arctic Middle Atmospheres: Their Differences and Similarities, 1999)
A number of campaigns have been conducted in order to study Polar Mesosphere Summer Echos (PMSE) and Noctilucent Clouds (NLC) in the period 1991–1994. Several sounding rockets have been launched through these layers with measurements being performed on upleg as well as downleg. These include measurements of positive ions and electrons in both ram and wake positions, as well as measurements of charged aerosols in ram on upleg. In this paper we will review these measurements and make a preliminary classification of the data based upon the presence of PMSE and/or NLC. One of the mechanisms responsible for PMSE is the presence of neutral air turbulence in combination with a high Schmidt number. We will briefly discuss this type of echo using in situ rocket data. Differences and similarities of PMSE and NLC as observed both in the Arctic and the Antarctic will be discussed. Observations show that especially PMSE are much more frequent in the Arctic. This may be due to a difference in the water vapour content or the temperature at mesopause heights. Lack of data in the Antarctic makes it difficult to decide which of these two factors are the most important. More measurements, especially co-ordinated in situ and ground-based lidar and radar measurements, are needed to discuss the Arctic and Antarctic similarities and differences in further detail.
Keywords: Antarktis; astrofysikk; atmosfæren; geofysikk; mesosfæren; meteorologi; polarområdene

The cryosphere: an early indicator and global player - Grassl, Hartmut (Polar Research, 1999)
Ice at or below the surface of the planet Earth is an important part of the climate system. The solid phase of water has two unique characteristics which make it both an early indicator of climate change and a global player. First, if warmed to the melting point at 0°C, higher air temperatures and/or higher long-wave back radiation just increase the melting rate but not - as with all other surfaces- the temperature, which stays at 0°C. Small icecaps and mountain glaciers thus become early indicators of a changed climate. Second. If seawater is cooled to the freezing point at about- 1.8"C. the sea ice formation process ejects salt causing the denser water to sink, thereby filling the global ocean interior with very cold water. The location where most of this deep convection occurs is strongly dependent on the freshwater balance and thus on the average salinity of ocean basins. Present ocean configuration and ocean topography, as well as precipitation distribution, make the northern North Atlantic more saline than any other high latitude ocean part and thus the site with most of this deep water formation. Sea ice formation is therefore of high significance for the European climate. Since it drives the near surface warm North Atlantic current northward off the European coast in compensation for southward deep water flow in the western Atlantic, northwestern Europe is warmer by about 4°C than the same latitudes on the eastern Pacific coast of America.
Keywords: Antarktis; isbreer; klimaendringer; kryosfæren; polarområdene; sjøvann; vann

Predicted present-day evolution patterns of ice thickness and bedrock elevation over Greenland and Antarctica - Huybrechts, Philippe; Le Meur, Emmanuel (Polar Research, 1999)
This paper discusses predicted evolution patterns of present-day changes of ice thickness, surface elevation, and bedrock elevation over the Greenland and Antarctic continents. These were obtained from calculations with dynamic 3-D ice sheet models which were coupled to a visco-elastic solid Earth model. The experiments were initialized over the last two glacial cycles and subsequently averaged over the last 200 years to obtain the current evolution. The calculations indicate that the Antarctic Ice Sheet is still adjusting to the last glacial-interglacial transition yielding a decreasing ice volume and a rising bedrock elevation of the order of several centimetres per year. The Greenland Ice Sheet was found to be close to a stationary state with a mean thickness change of only a few millimetres per year, but the calculations revealed large spatial differences. Predicted patterns over Greenland are characterized by a small thickening over the ice sheet interior and a general thinning of the ablation area. In Antarctica, almost all of the predicted changes are concentrated in the West Antarctic Ice Sheet, which is still retreating at both the Weddell and Ross Sea margins. Over most of both ice sheets, the model indicates that the surface elevation trend is dominated by ice thickness changes rather than by bedrock elevation changes.
Keywords: Antarktis; glasiologi; innlandsis; polarområdene

The Antarctic contribution to Holocene global sea level rise - Ingólfsson, Ólafur; Hjort, Christian (Polar Research, 1999)
The Holocene glacial and climatic development in Antarctica differed considerably from that in the Northern Hemisphere. Initial deglaciation of inner shelf and adjacent land areas in Antarctica dates back to between 10-8 Kya, when most Northern Hemisphere ice sheets had already disappeared or diminished considerably. The continued deglaciation of currently ice-free land in Antarctica occurred gradually between ca. 8-5 Kya. A large southern portion of the marine-based Ross Ice Sheet disintegrated during this late deglaciation phase. Some currently ice-free areas were deglaciated as late as 3 Kya. Between 8-5 Kya, global glacio-eustatically driven sea level rose by 10-17m, with 4-8 m of this increase occurring after 7 Kya. Since the Northern Hemisphere ice sheets had practically disappeared by 8-7 Kya, we suggest that Antarctic deglaciation caused a considerable part of the global sea level rise between 8-7 Kya, and most of it between 7-5 Kya. The global mid-Holocene sea level high stand, broadly dated to between 8-4 Kya, and the Littorina-Tapes transgressions in Scandinavia and simultaneous transgressions recorded from sites e.g. in Svalbard and Greenland, dated to 7-5 Kya, probably reflect input of meltwater from the Antarctic deglaciation.
Keywords: Antarktis; geologi; glasiologi; havnivåstigning; innlandsis; paleoglasiologi; polarområdene

Antarktis : norsk natur- og kulturminneforvaltning - Njåstad, Birgit (ed.) (Norsk Polarinstitutt, 1999)
Keywords: Antarktis; Norge; forvaltning; kulturminneforvaltning; miljøvern; naturforvaltning; naturvern; polarområdene

Global change and the polar regions - Rapley, Chris (Polar Research, 1999)
Keywords: Antarktis; klimaendringer; polarområdene

A global model tool for three-dimensional multiyear stratospheric chemistry simulations: Model description and first results - Rummukainen, Markku; Isaksen, Ivar S A; Rognerud, Bjørg; Stordal, Frode (Journal of Geophysical Research: Atmospheres, 1999)
The paper presents a new global modeling tool, Stratospheric Chemical Transport Model 2. It has been developed for effective three-dimensional multiyear stratospheric chemistry studies, featuring an extensive chemistry scheme, heterogeneous processing on sulfate aerosols, and some polar stratospheric cloud processes. The transport algorithm maintains sub-grid-scale distributions and connects vertically the stratospheric layers, even in a coarse vertical grid. The model has been integrated for 49 months, recycling 1 year of precalculated transport from a middle atmosphere general circulation model. One year of daily National Centers for Environmental Prediction global analyses are used as temperatures. Diurnal cycles of photolysis rates are recalculated every 7 days to give interaction with ozone changes. The model is able to describe most of the geographical and seasonal ozone variability and the meridional distributions of ozone, reactive nitrogen, chlorine, and bromine. Stratospheric diurnal cycles for nitrogen, hydrogen, chlorine, and bromine species are captured in detail. The upper stratosphere ozone deficiency, typical to models, is large. Its sensitivity to different ways of tuning are explored. Midlatitude, rather than polar, wintertime processes have so far been the focus in this model tool. The present transport and grid resolution are not suited for realistic simulations at high latitudes. As there is only a limited inclusion of polar stratospheric cloud (PSC) microphysics, chemical processing in the cold polar lower stratosphere also cannot be well simulated. For example, the Antarctic ozone hole is not simulated, but the modeled chemistry should be suitable for warm Arctic winters when type II PSCs and particle sedimentation do not occur.
Keywords: Antarktis; geofysikk; meteorologi; ozonlaget; polarområdene; stratosfæren; stratosfærisk kjemi

Residue determinants and sequence analysis of cold-adapted trypsins - Schrøder Leiros, Hanna-Kirsti; Willassen, Nils Peder; Smalås, Arne O. (Extremophiles, 1999)
The digestive enzyme trypsin is among the most extensively studied proteins, and its structure has been reported from a large number of organisms. This article focuses on the trypsins from vertebrates adapted to life at low temperatures. Cold-adapted organisms seem to have compensated for the reduced reaction rates at low temperatures by evolving more active and less temperature-stable enzymes. We have analyzed 27 trypsin sequences from a variety of organisms to find unique attributes for the cold-adapted trypsins, comparing trypsins from salmon, Antarctic fish, cod, and pufferfish to other vertebrate trypsins. Both the "cold" and the "warm" active trypsins have about 50 amino acids that are unique and conserved within each class. The main unique features of the cold-adapted trypsins attributable to low-temperature adaptation seem to be (1) reduced hydrophobicity and packing density of the core, mainly because of a lower (Ile + Leu)/(Ile + Leu + Val) ratio, (2) reduced stability of the C-terminal, (3) lack of one warm trypsin conserved proline residue and one proline tyrosine stacking, (4) difference in charge and flexibility of loops extending the binding pocket, and (5) different conformation of the "autolysis" loop that is likely to be involved in substrate binding.
Keywords: Sørishavet; biokjemi; fisker; marin biologi; mikrobiologi; polarområdene

The interplay of global and polar regimes - Young, Oran R. (Polar Research, 1999)
The growing salience of interactions between the functionally broad but geographically narrow regimes for the polar regions and the geographically broad but functionally specific regimes emerging to deal with global environmental changes directs attention to the issue of institutional interplay. Interplay among regimes can cause mutual interference or foster synergy. Adopting a pragmatic stance that assumes no fundamental changes in international society, this essay suggests ways to: (1) adapt global regimes dealing with ozone depletion, climate change and biodiversity to the conditions prevailing in the polar regions; and (2) ensure that concerns arising in the polar regions receive serious consideration in global forums. Specific suggestions range from modest initiatives involving monitoring and assessment to more ambitious initiatives, such as the establishment of a chamber of regions in global regimes.
Keywords: Antarktis; biodiversitet; internasjonal samarbeid; klimaendringer; klimapolitikk; ozonlaget; polarområdene

Sixty year 10Be record from Greenland and Antarctica - Aldahan, A.; Possnert, G.; Johnsen, S. J.; Clausen, H. B.; Isaksson, Elisabeth; Karlen, W.; Hansson, M. (Proceedings of the Indian Academy of Sciences - Earth and Planetary Sciences, 1998)
We report in this study the distribution of 10Be in the top 40 m of the Renland ice core (East Greenland) and in a 30 m long core from DML (Dronning Maud Land, Antarctica) for the period 1931–1988. The two sites show differences in10Be content, the Antarctica site showing smaller variance and a lower average 10Be annual flux. Similarly, the average accumulation rate (cm water equivalent year−1) is higher in the Renland relative to DML. The variability in accumulation (precipitation) rates seems to explain part of the difference in10Be flux between the two polar sites. Cyclic fluctuations of 10Be flux correlate with the 11-year sunspot number and cosmic ray intensity than with the aa index (perturbation of the geomagnetic activity by the solar wind). Our data corroborate 10Be cyclic fluctuation pattern from the Dye 3 ice core and confirm a promising potential for correlation of global and local events.
Keywords: Dronning Maud Land; glasiologi; iskjerner; klimatologi; meteorologi; polarområdene

Norway and the polar regions - Hansson, Rasmus (The Royal Norwegian Ministry of Foreign Affairs, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Norge og polarområdene - Hansson, Rasmus (ed.) (Utenriksdepartementet, 1998)
Keywords: Antarktis; Norge; geografi; historie; miljøvern; polarforskning; polarområdene; politikk

Ambient air levels and atmospheric long-range transport of persistent organochlorines to Signy Island, Antarctica - Kallenborn, Roland; Oehme, Michael; Wynn-Williams, David D; Schlabach, Martin; Harris, Joyce (Science of The Total Environment, 1998)
Levels of persistent organic pollutants (POPs), such as polychlorinated biphenyls and pesticides have been determined in ambient air at Signy Island, Antarctica, over a period of 17 weeks. Mean concentrations for single polychlorinated biphenyls (0.02–17 pg/m3), for chlordanes (0.04–0.9 pg/m3), DDT compounds (0.07–0.40 pg/m3) and γ-hexachlorocyclohexane (HCH, 22 pg/m3) were comparable to those in Arctic air. However, α-HCH levels were approximately one order of magnitude lower. Compared to the Arctic, differences were also observed in the concentration ratios of α-/γ-HCH and chlordane compounds. Two possible atmospheric long-range transport episodes from South America were found by comparing 10-day back trajectories with observed concentration changes. The lower limits of determination (LOD) were mainly governed by the field blanks. They were satisfactory for the most volatile PCBs. However, many concentrations for DDT and chlordane compounds were below the LODs (range 0.1–1 pg/m3) or even the instrumental detection limit (0.01–0.03 pg/m3).
Keywords: Antarktis; atmosfæren; forurensning; langtransport; luftforurensning; meteorologi; miljøgifter; polarområdene

Establishing chronologies from acid-insoluble organic 14C dates on Antarctic (Ross Sea) and Arctic (North Atlantic) marine sediments - Licht, Kathy J; Cunningham, Wendy L; Andrews, John T; Domack, Eugene W; Jennings, Anne E (Polar Research, 1998)
Keywords: Rosshavet; Sørishavet; paleoseanografi; polarområdene; sedimentologi

A Comparison of the CCM3 Model Climate Using Diagnosed and Predicted Condensate Parameterizations - Rasch, Philip J.; Kristjánsson, Jón Egill (Journal of Climate, 1998)
A parameterization is introduced for the prediction of cloud water in the National Center for Atmospheric Research Community Climate Model version 3 (CCM3). The new parameterization makes a much closer connection between the meteorological processes that determine condensate formation and the condensate amount. The parameterization removes some constraints from the simulation by allowing a substantially wider range of variation in condensate amount than in the standard CCM3 and tying the condensate amount to local physical processes. The parameterization also allows cloud drops to form prior to the onset of grid-box saturation and can require a significant length of time to convert condensate to a precipitable form, or to remove the condensate. The free parameters of the scheme were adjusted to provide reasonable agreement with top of atmosphere and surface fluxes of energy. The parameterization was evaluated by a comparison with satellite and in situ measures of liquid and ice cloud amounts. The effect of the parameterization on the model simulation was then examined by comparing long model simulations to a similar run with the standard CCM and through comparison with climatologies based upon meteorological observations. Global ice and liquid water burdens are higher in the revised model than in the control simulation, with an accompanying increase in height of the center of mass of cloud water. Zonal averages of cloud water contents were 20%–50% lower near the surface and much higher above. The range of variation of cloud water contents is much broader in the new parameterization but was still not as large as measurements suggest. Differences in the simulation were generally small. The largest significant changes found to the simulation were seen in polar regions (winter in the Arctic and all seasons in the Antarctic). The new parameterization significantly changes the Northern Hemisphere winter distribution of cloud water and improves the simulation of temperature and cloud amount there. Small changes were introduced in the cloud fraction to improve consistency of the meteorological parameterizations and to attempt to alleviate problems in the model (in particular, in the marine stratocumulus regime). The small changes did not make any appreciable improvement to the model simulation. The new parameterization adds significantly to the flexibility in the model and the scope of problems that can be addressed. Such a scheme is needed for a reasonable treatment of scavenging of atmospheric trace constituents, and cloud aqueous or surface chemistry. The addition of a more realistic condensate parameterization provides opportunities for a closer connection between radiative properties of the clouds, and their formation and dissipation. These processes must be treated for many problems of interest today (e.g., anthropogenic aerosol–climate interactions).
Keywords: Antarktis; klimamodeller; klimatologi; meteorologi; polarområdene

Stability of the Thermohaline Circulation to Noisy Surface Buoyancy Forcing for the Present and a Warm Climate in an Ocean General Circulation Model - Skagseth, Øystein; Mork, Kjell Arne (Journal of Physical Oceanography, 1998)
The stabilities of two different circulation regimes in the North Atlantic, 1) the present thermohaline circulation and 2) a weaker thermohaline circulation, are compared using the Hamburg Large Scale Geostrophic (LSG) ocean circulation model. The latter circulation regime is obtained by restoring the LSG model toward an on average 48C warmer air surface temperature corresponding to a doubled atmospheric content of CO 2 . The stabilities of these stationary states are investigated by imposing various amounts of stochastic noise on the surface freshwater flux. The simulations show more variability on secular timescales for the present than for the warm climate. Since the modeled static stabilities for the two climates are relatively similar, the different rates of variability are probably connected to other mechanisms. In the present climate at high latitudes the two buoyancy fluxes due to heat and freshwater are of similar magnitudes but with opposite signs; thus switches between convective and nonconvective periods at secular timescales are possible. In the warm climate the buoyancy flux due to heat dominates. This compensates the effect of the noisy freshwater forcing and thus reduces the potential for secular oscillations. The stronger coupling between the Atlantic and the Southern Ocean for the present relative to the warm climate could also contribute to this difference. Furthermore, the simulations show that the variability of the Antarctic Circumpolar Current transport for the present climate exceeds that of the warm climate. For increasing stochastic noise the present circulation approaches that of the warm circulation. The authors apply a mixture of heat flux and temperature restoring for the surface boundary condition. Comparison with similar works, which apply a pure restoring for surface temperature, shows that the ocean circulation is much less sensitive to forced stochastic freshwater anomalies with the type of boundary condition used herein. A box model is used to illustrate the effects of the surface temperature parameterizations and the different buoyancy forcing for the present and warm climate.
Keywords: AABW; Sørishavet; Sørishavsstrømmen; geofysikk; havstrømmer; oseanografi; polarområdene; vannmasser

Validation of Ground-Based Visible Measurements of Total Ozone by Comparison with Dobson and Brewer Spectrophotometers - Van Roozendael, Michel; Peeters, P.; Roscoe, H. K.; De Backer, H.; Jones, A. E.; Bartlett, L.; Vaughan, G.; Goutail, Florence; Pommereau, Jean-Pierre; Kyro, E.; Wahlstrom, C.; Braathen, Geir; et al. (Journal of Atmospheric Chemistry, 1998)
Comparisons of total column ozone measurements from Dobson, Brewer and SAOZ instruments are presented for the period 1990 to 1995 at seven stations covering the mid- and the high northern latitudes, as well as the Antarctic region. The main purpose of these comparisons is to assess, by reference to the well established Dobson network, the accuracy of the zenith-sky visible spectroscopy for the measurement of total ozone. The strengths and present limitations of this latter technique are investigated. As a general result, the different instruments are found to agree within a few percent at all stations, the best agreement being obtained at mid-latitudes. On average, for the mid-latitudes, SAOZ O3 measurements are approximately 2% higher than Dobson ones, with a scatter of about 5%. At higher latitudes, both scatter and systematic deviation tend to increase. In all cases, the relative differences between SAOZ and Dobson or Brewer column ozone are characterised by a significant seasonal signal, the amplitude of which increases from about 2.5% at mid-latitude to a maximum of 7.5% at Faraday, Antarctica. Although it introduces a significant contribution to the seasonality at high latitude, the temperature sensitivity of the O3 absorption coefficients of the Dobson and Brewer instruments is shown to be too small to account for the observed SAOZ/Dobson differences. Except for Faraday, these differences can however be largely reduced if SAOZ AMFs are calculated with realistic climatological profiles of ozone, pressure and temperature. Other sources of uncertainties that might affect the comparison are investigated. Evidence is found that the differences in the air masses sampled by the SAOZ and the other instruments contribute significantly to the scatter, and the impact of the tropospheric clouds on SAOZ measurements is displayed.
Keywords: Antarktis; klimatologi; ozon; polarområdene; spektrofotometri; stratosfæren

Experimental formation of sea ice: importance of water circulation and wave action for incorporation of phytoplankton and bacteria - Weissenberger, Jürgen; Grossmann, Sönnke (Polar Biology, 1998)
The efficiency of physical concentration mechanisms for enrichment of algae and bacteria in newly formed sea-ice was investigated under defined conditions in the laboratory. Sea-ice formation was simulated in a 3,000 l tank under different patterns of water movement. When ice formed in an artificially generated current pattern, algal cells were substantially enriched within the ice matrix. Enrichment factors for chlorophyll a calculated from the ratio between the concentrations in ice and underlying water reached values of up to 53. Repeated mixing of ice crystals into the water column, as well as flow of water through the new ice layer, contributed to the enrichment of algae in the ice. Wave action during ice formation revealed lower phytoplankton enrichment factors of up to 9. Mixing of floating ice crystals with underlying water and pumping of water into the ice matrix by periodical expansion and compression of the slush ice layer were responsible for the wave-induced enrichment of algal cells. Physical enrichment of bacteria within the ice was negligible. Bacterial biomass within new ice was enhanced only when the concentration of algae was high. At low algal biomass, bacteria experienced substantial losses in the ice, most likely due to brine drainage, which were not observed for the microalgae. Bacterial cells are therefore not scavenged by ice crystals and the observed enrichment and sustainment of bacterial biomass within newly formed ice depend on their attachment to cells or aggregates of algae. Division rates of bacteria changed only slightly during ice formation.
Keywords: Sørishavet; Weddellhavet; alger; bakterier; fytoplankton; havis; marin biologi; polarområdene

Analysis of merged SMMR-SSMI time series of Arctic and Antarctic sea ice parameters 1978–1995 - Bjørgo, Einar; Johannessen, Ola M.; Miles, Martin W. (Geophysical Research Letters, 1997)
The most consistent means of investigating the global sea ice cover is by satellite passive microwave sensors, as these are independent of illumination and cloud cover. The Nimbus 7 Scanning Multichannel Microwave Radiometer (SMMR) and the Defense Meteorological Satellite Program (DMSP) Special Sensor Microwave Imager (SSMI) provide information on the global sea ice cover from 1978 to present. The two instruments flew simultaneously during a 6-week overlap period in July and August 1987, thus enabling intercomparison of the two sensors. Brightness temperatures are corrected for instrument drift and calibration differences in order to produce continuous time series of monthly averaged Arctic and Antarctic sea ice extent and sea ice area through the use of the NOrwegian Remote Sensing EXperiment (NORSEX) algorithm, which relates brightness temperatures to ice concentration. Statistical analysis on the time series estimates the decreases in Arctic ice extent and ice area to be 4.5% and 5.7%, respectively, during the 16.8-year observation period. The overall trends established here serve to better define and strengthen earlier assertions of a reduced ice cover, based on analysis of SMMR and SSMI data taken separately. These results are consistent with GCM simulations that suggest retreat of the sea ice cover under global warming scenarios.
Keywords: Antarktis; global oppvarming; havis; klimaendringer; meteorologi; polarområdene; satellite mikrobølgesensorer

Et større Norge 1949-65 - Eriksen, Knut Einar (Kald krig og internasjonalisering, 1949-1965, 1997)
Keywords: Antarktis; Norge; historie; internasjonal; polarområdene; politikk; utenrikspolitikk

Cold resistance and metabolic activity of lichens below 0°C - Kappen, Ludger; Schroeter, Burkhard; Scheidegger, Christoph; Sommerkorn, Martin; Hestmark, Geir (Proceedings of the F3.1, F3.4, F2.4 and F3.8 Symposia of COSPAR Scientific Commission F, 1996)
Laboratory measurements show that lichens are extremely tolerant of freezing stress and of low-temperature exposure. Metabolic activity recovered quickly after severe and extended cold treatment. Experimental results demonstrate also that CO2 exchange is already active at around −20°C. The psychrophilic character of polar lichen species is demonstrated by optimum temperatures for net photosynthesis between 0 and 15°C. In situ measurements show that lichens begin photosynthesizing below 0°C if the dry thalli receive fresh snow. The lowest temperature measured in active lichens was −17°C at a continental Antarctic site. The fine structure and the hydration state of photobiont and mycobiont cells were studied by low-temperature scanning electron microscopy (LTSEM) of frozen hydrated specimens. Water potentials of the frozen system are in the range of or even higher than those allowing dry lichens to start photosynthesis by water vapor uptake at +10°C. The great success of lichens in polar and high alpine regions gives evidence of their physiological adaptation to low temperatures. In general lichens are able to persist through glacial periods, but extended snow cover and glaciation are limiting factors.
Keywords: Antarktis; botanikk; frostresistens; lav; planter; polarområdene

Lack of population subdivision among the minke whales (Balaenoptera acutorostrata) from Icelandic and Norwegian waters based on mitochondrial DNA sequences - Bakke, Ingrid; Johansen, Steinar; Bakke, [Øyvind]; El-Gewely, Mohamed Raafat (Marine Biology, 1996)
The minke whale (Balaenoptera acutorostrata) is subject to commercial whaling, but stock identification and assessment are still uncertain. Mitochondrial DNA (mtDNA) sequences were determined to examine the population structure of minke whales from the central and northeastern parts of the North Atlantic, as well as the Antarctic regions IV and V. The analyses include 345 nucleotide positions of the control region of 110 individuals, and 250 nucleotide positions of the NADH dehydrogenase subunit 2 gene for a representative selection of North Atlantic minke whales. Maximum parsimony analyses and sequence divergence calculations did not reveal any genetic differentiation between individuals from the central and northeastern parts of the North Atlantic. These results do not support the International Whaling Commission's separation of minke whales in this area into different management units, and they are in conflict with previously reported results from allozyme analyses. Comparison of minke whale control region sequences showed that the sequence diversity of North Atlantic minke whales is substantially lower (0.0065) than that of Antarctic minke whales (0.0166), and clearly demonstrated that individuals from these two areas represent genetically distinct populations.
Keywords: Sørishavet; bioteknologi; genetikk; hvaler; marin biologi; polarområdene

Territoriell ekspansjonspolitikk - Fure, Odd-Bjørn (Mellomkrigstid : 1920-1940, 1996)
Keywords: Antarktis; Norge; historie; internasjonal; norske ekspedisjoner; polarområdene; politikk; utenrikspolitikk

Dagbok fra Sydpolen - Johansen, Hjalmar (Vågemot forl., 1996)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Anhydrobiosis and cold tolerance in tardigrades - Sømme, Lauritz (European Journal of Entomology, 1996)
A review of the literature regarding anhydrobiosis and cold tolerance in tardigrades is presented. During increasing desiccation, invertebrates like tardigrades, rotifers, nematodes and some collembolans are able to shut down metabolism to undetectable levels. When tardigrades are entering anhydrobiosis, a tun-like structure is formed, facilitated by structural adaptations of the cuticle. Slow dehydration is essential for tun formation, and the accumulation of trehalose during this process may help to stabilize phospholipids and proteins. Wax extrusion on the cuticle surface reduces transpiration. A fraction of 5-15% of the initial body water is retained during anhydrobiosis. Tardigrades are principally aquatic organisms, but anhydrobiosis makes it possible for some species to live in habitats with changing moisture conditions. Tardigrades in anhydrobiosis may tolerate exposure to freezing temperatures of liquid gases, and some species also survive such temperatures in their hydrated state. Few investigations are available on the relation of tardigrades to temperatures more representative to their natural environments. Experimental studies, however, from Greenland and the Antarctic Continent suggest that some species overwinter both in a hydrated frozen state and in anhydrobiosis. During the summer, a number of tardigrade species have been recorded from cryoconite holes, formed on the surface of glaciers. These species are freeze tolerant since their habitats are permanently frozen during the winter.
Keywords: Antarktis; Dronning Maud Land; biomonitorering; bjørnedyr; entomologi; kuldetoleranse; polarområdene; virvelløse dyr

Effects of UV radiation on post-bloom phytoplankton populations in Kvalsund, North Norway - Walter Helbling, E.; Eilertsen, Hans Chr.; Villafañe, Virginia E.; Holm-Hansen, Osmund (Journal of Photochemistry and Photobiology B: Biology, 1996)
Our studies in the coastal waters in North Norway show that rates of photosynthesis of natural phytoplankton assemblages are strongly inhibited by solar UV radiation. When exposed to high irradiances of direct solar radiation, photosynthetic rates were increased by approximately 150% when all UV radiation was excluded from samples, with UVB radiation being responsible for approximately 50% of the total inhibition. There was no discernible threshold value for inhibition of photosynthesis by UV radiation, even at UV (280–400 nm) irradiances as low as 0.1 W m−2. When natural assemblages were incubated in situ, inhibition of photosynthetic rates were detectable down to 10 m, where solar irradiance was about 3% of the radiation incident on the sea surface. Based on the inhibition of photosynthetic rates at very low fluences of UV radiation, post-bloom assemblages of phytoplankton in North Norway and possibly also in the Arctic ocean appear to be more sensitive to solar UV radiation than phytoplankton from the Southern Ocean.
Keywords: Sørishavet; fotosyntese; fytoplankton; marin biologi; polarområdene; ultrafiolett stråling

Norges polare interesser - Berg, Roald (Norge på egen hånd, 1995)
Keywords: Antarktis; Norge; historie; polarområdene; utenrikspolitikk

Polychlorinated Dibenzo-p-Dioxins, Dibenzofurans and Coplanar Biphenyls in Antarctic Fur Seal Blubber - Oehme, Michael; Schlabach, Martin; Boyd, Ian (Ambio, 1995)
Levels of polychlorinated dibenzo-p-dioxins (PCDD) and dibenzofurans (PCDF) as well as of coplanar (non-ortho substituted) polychlorinated biphenyls (CB-77, CB-126 and CB-169) have been determined in 11 fur-seal blubber samples from female Antarctic fur seals. Measurable PCDD/PCDF concentrations averaging 2 ppt TEQ (Nordic model) were found. This is considerably less than in Arctic seals. In addition, the PCDD/PCDF congener patterns differed between Antarctic and Arctic seals. The levels of CB-77, CB-126 and CB-169 (8.5-41 pg g-1 for single congeners in average) in Antarctic fur seals were also much lower than in Arctic ringed and harp seals. A possible explanation of these differences is the overall lower environmental pollution of the Southern Hemisphere, though an influence of different age and sex distributions cannot be excluded. The data passed all quality assurance criteria that had been established for such low levels.
Keywords: Antarktis; forurensning; marin biologi; miljøgifter; pinnipedier; polarområdene; seler

Norske offentlige samlinger med kulturhistorisk polarmateriale - Barr, Susan (Norsk polarinstitutt, 1994)
Keywords: Antarktis; polarforskning; polarhistorie; polarområdene; polarsamlinger

Rock mapping of glaciated areas by satellite image processing - Salvini, Francesco; Della Maggiore, Roberto; Fortunati, Luciano; Mazzarini, Francesco (Polar Research, 1994)
Keywords: Antarktis; geologi; polarområdene; satellitt bilder

Ecology of sea ice biota. 1. Habitat, terminology, and methodology - Horner, Rita; Ackley, Stephen F.; Dieckmann, Gerhard S.; Gulliksen, Bjorn; Hoshiai, Takao; Legendre, Louis; Melnikov, Igor A.; Reeburgh, William S.; Spindler, Michael; Sullivan, Cornelius W. (Polar Biology, 1992)
Polar regions are covered by extensive sea ice that is inhabited by a variety of plants and animals. The environments where the organisms live vary depending on the structure and age of the ice. Many terms have been used to describe the habitats and the organisms. We here characterize the habitats and communities and suggest some standard terms for them. We also suggest routine sampling methods and reporting units for measurements of biological and chemical variables.
Keywords: Sørishavet; biodiversitet; havis; marin biologi; polarområdene; økologi

Ecology of sea ice biota. 2. Global significance - Legendre, Louis; Ackley, Stephen F.; Dieckmann, Gerhard S.; Gulliksen, Bjørn; Horner, Rita; Hoshiai, Takao; Melnikov, Igor A.; Reeburgh, William S.; Spindler, Michael; Sullivan, Cornelius W. (Polar Biology, 1992)
The sea ice does not only determine the ecology of ice biota, but it also influences the pelagic systems under the ice cover and at ice edges. In this paper, new estimates of Arctic and Antarctic production of biogenic carbon are derived, and differences as well as similarities between the two oceans are examined. In ice-covered seas, high algal concentrations (blooms) occur in association with several types of conditions. Blooms often lead to high sedimentation of intact cells and faecal pellets. In addition to ice-related blooms, there is progressive accumulation of organic matter in Arctic multi-year ice, whose fate may potentially be similar to that of blooms. A fraction of the carbon fixed by microalgae that grow in sea ice or in relation to it is exported out of the production zone. This includes particulate material sinking out of the euphotic zone, and also material passed on to the food web. Pathways through which ice algal production does reach various components of the pelagic and benthic food webs, and through them such top predators as marine mammals and birds, are discussed. Concerning global climate change and biogeochemical fluxes of carbon, not all export pathways from the euphotic zone result in the sequestration of carbon for periods of hundreds of years or more. This is because various processes, that take place in both the ice and the water column, contribute to mineralize organic carbon into CO2 before it becomes sequestered. Processes that favour the production and accumulation of biogenic carbon as well as its export to deep waters and sequestration are discussed, together with those that influence mineralization in the upper ice-covered ocean.
Keywords: Sørishavet; biodiversitet; biogeokjemi; havis; karbondioksid; klimaendringer; marin biologi; polarområdene; økologi

The ecophysiology of under-ice fauna - Aarset, Arne V (Polar Research, 1991)
Keywords: Antarktis; amfipoder; fauna; havis; polarområdene; sjøis; zoologi; økofysiologi

The physiology of polar marine zooplankton - Clarke, Andrew; Peck, Lloyd S (Polar Research, 1991)
Keywords: Sørishavet; marin biologi; polarområdene; zooplankton

Occurrence of polar seabirds at sea in relation to prey concentrations and oceanographic factors - Hunt Jr, George L (Polar Research, 1991)
Keywords: Antarktis; næring; ornitologi; oseanografi; polarområdene; sjøfugler; økosystemer

Light and productivity of phytoplankton in polar marine ecosystems: a physiological view - Sakshaug, Egil; Slagstad, Dag (Polar Research, 1991)
Keywords: Sørishavet; fysiologi; fytoplankton; planteplankton; polarområdene

Sandefjord - et naturlig polarforskningssenter - Wexelsen, Einar (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1991)
Keywords: Antarktis; Norsk Polarinstitutt; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

The pelagic distribution of marine birds in a heterogeneous environment - Hunt Jr, George L. (Polar Research, 1990)
Keywords: Antarktis; fugler; marin ornitologi; næring; polarområdene

The pelagic distribution of marine birds in a heterogeneous environment - Hunt Jr, George L (Polar Research, 1990)
Keywords: Antarktis; fugler; ornitologi; polarområdene; zoologi

Virkninger av klimaendringer i polarområdene : bidrag til den interdepartementale klimautredningen - Kverndal, Arnt-Ivar; Elvebakk, Arve; Jaworowski, Zbygniew; Hansson, Rasmus (Norsk Polarinstitutt, 1990)
Keywords: Antarktis; biologi; drivhuseffekten; dyreliv; fiskeri; flora; havbruksnæring; havis; havnivå; isbreer; klimaendringer; klimagasser; permafrost; planter; polarområdene; vannressurser; økologi

Some Nitzschia and related diatom species from fast ice samples in the Arctic and Antarctic - Medlin, Linda K.; Hasle, Grethe Rytter (Polar Biology, 1990)
Some Nitzschia and closely related species have been examined in the light and electron microscopes from fast ice samples in the Arctic and Antarctic. Nitzschia neofrigida, forming arborescent colonies, and Nitzschia promare, forming loose ribbon colonies, are described as new species, both probably included in the distribution of other similar species. A new combination, Auricula compacta, represents the first report of this genus from ice samples. Colony formation is reported for the first time in Nitzschia arctica and Nitzschia taeniiformis. No biopolar species were found and several reports of Arctic species in Antarctic ice samples have been refuted.
Keywords: Antarktis; alger; biodiversitet; biologi; botanikk; diatomeer; fytoplankton; planteplankton; polarområdene

A hundred years of Norwegian exploration of the polar regions - Orheim, Olav (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1989)
Keywords: Antarktis; Norge; ekspedisjoner; oppdagelsesreiser; polarområdene

Hva skjer med klimaet i polarområdene? : sammendrag av foredrag på symposium 25-26 april 1989 - Orheim, Olav (ed.); Brekke, Annemor (ed.) (Norsk Polarinstitutt, 1989)
Keywords: Antarktis; global oppvarming; klimaendringer; polarområdene; symposium

Proposed terminology and reporting units for sea ice algal assemblages - Horner, Rita A; Syvertsen, Erik E; Thomas, David P; Lange, Carina (Polar Biology, 1988)
Keywords: Antarktis; alger; havis; marin biologi; polarområdene; sjøis

Sydpolen 1910-1912 - Huntford, Roland; Hoff, Truls (Roald Amundsens oppdagelsesreiser i bilder, 1988)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; forskning; fotografihistorie; historie; oppdagelsesreiser; polarområdene

Norway's polar territories - Barr, Susan (Aschehoug, 1987)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Peter I. Øy; geografi; geologi; historie; polarområdene; polarpolitikk

Zonality of climate and plant distributions in some Arctic and Antarctic regions - Engelskjøn, Torstein (Norsk Polarinstitutt, 1986)
Keywords: Bouvetøya; Dronning Maud Land; botanikk; klima; planter; polarområdene

Aleksandr Stepanovich Kuchin: the Russian who went south with Amundsen - Barr, William (Polar Record, 1985)
Aleksandr Stepanovich Kuchin (1888–1912) was already an experienced mariner and oceanographer when Amundsen invited him to join the Fram expedition of 1910–12. Expecting a voyage through the Barents Sea, Kuchin found himself on an expedition to the Antarctic. While Amundsen's sledging parties sought the South Pole, Kuchin remained with the ship, completing an excellent oceanographic survey of the southern Atlantic Ocean. Returning to Russia in 1912 he was recruited, by the geologist and explorer V. A. Rusinov to join a scientific expedition to Svalbard. As deputy leader of the party and captain of Gerkules, the expedition ship, Kuchin played an important role in the Svalbard survey. Then once again found himself heading in an unexpected direction: on completing the Svalbard work, Rusanov decided to attempt the Northern Sea Route to the Bering Strait. Gerkules disappeared and was never seen again; her loss, presumably in the Kara Sea, brought to an untimely end the career of a promising young polar explorer.
Keywords: Roald Amundsen; Sydpolsekspedisjonen; Sørishavet; biografier; oseanografi; polarområdene

Norge i polarområdene - Egeland, Knut (Leif Holtedahls forl., 1982)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Scott og Amundsen - Huntford, Roland; Christensen, Jan (Aschehoug, 1980)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Eventyret Antarktis - Børde, Haakon; Johansen, Karl Hans (Gyldendal, 1978)
Keywords: Antarktis; Norge; Norsk Polarinstitutt; Sydpolsekspedisjonen; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Med Amundsen til Sudpolen. Dagbokblad - Bjaaland, Olav (Syn og segn, 1975)
Keywords: Antarktis; Roald Amundsen; Sydpolen; dagbok; ekspedisjoner; oppdagelsesreiser; polarområdene

Norsk polarpolitikk : hovedtrekk og utviklingslinjer 1905-1974 - Skagestad, Odd Gunnar (Dreyers Forlag, 1975)
Keywords: Antarktis; Norge; historie; polarforskning; polarområdene; polarpolitikk; statsforvaltning

The New Development in the Polar Regions - Sollie, Finn (Cooperation and Conflict, 1974)
Due to factors connected with modern technological developments and with the increasing global demand for new sources of raw materials, there is today a growing interest in the possibilities for economic exploitation of the polar regions. This makes for a new development in these regions; a development comprising and affecting such fields as science and technology as well as economy, transportation, military strategy and ecology. The present paper discusses this new development and its implications in an international perspective. Special attention is paid to the significance - in the physical/ geographical sense and otherwise - of the polar regions in the global context. A special section deals, on a general level, with 'the problem of the new territories', and the polar regions are discussed as new territories. Pointing out the risks and dangers inherent in the present and emerging developments, the author emphasizes the need for action, especially international cooperation, to meet and solve such problems. Cooperation may be facilitated through regular consultations between the states concerned, as is the case under the Antarctic Treaty. For the Arctic in particular, the author suggests a distinction between three basic zones (viz. the 'Central' the 'Intermediate' and the 'National' Arctic) as a possible point of departure for future discussion of measures of international cooperation.
Keywords: Antarktis; internasjonal politikk; polarområdene

Kappløpet mot Sydpolen - Jonason, Jan (Tiden, 1971)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

In Amundsen's Tracks on the Axel Heiberg Glacier - Herbert, Walter William (The Geographical Journal, 1963)
Keywords: Antarktis; Roald Amundsen; ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Benthonic problems in Antarctic and Arctic waters - Broch, Hjalmar (Aschehoug, 1961)
Keywords: Norvegia ekspedisjoner; Sørishavet; marin biologi; polarområdene; zoogeografi

Femti år for Kongen - Riiser-Larsen, Hjalmar (Gyldendal, 1957)
Keywords: Antarktis; Hjalmar Riiser; Larsen; biografier; ekspedisjoner; geografi; kartlegging; luftfart; oppdagelsesreiser; polarforskning; polarområdene

Norske fangfstfolk og forskere i Antarktis. Den Tredje Framferda (1910-12). Mot Nordpolen via Sørpolen. Roald Amundsen planter den norske flagget på Sørpolen 14.-12.-1911 - Opsund, Enok (Nordmenn i polheimene, 1948)
Keywords: Antarktis; Nordmenn; Roald Amundsen; Sydpolsekspedisjonen; ekspedisjoner; fangst; forskning; polarområdene

Sydpolens helter - Andersson, Johan Gunnar; Werner-Johanessen, Thor; Balchen, Bernt; Bogen, Hans (Cammermeyer, 1947)
Keywords: Antarktis; Roald Amundsen; historie; oppdagelsesreiser; polarekspedisjoner; polarområdene

Die südpolaren Gebiete - Smedal, Gustav (Souveränitätsfragen der Polargebiete : norwegische Interessen in den Eismeeren, 1943)
Keywords: Antarktis; Bouvetøya; Norge; Peter I. Øy; internasjonal; polarområdene; politikk; rett

Norges interesser i polartraktene - Hoel, Adolf (Gunnar Stenersen, 1942)
Keywords: Antarktis; polarforskning; polarområdene; polarpolitikk

Pelagic whaling in the Antarctic : 9 : The season 1938-1939 - Bergersen, Birger; Ruud, Johan T (I kommisjon hos Dybwad, 1941)
Keywords: Sørishavet; hvaler; hvalfangst; pelagisk; polarområdene

Gjennem isbaksen : atten år med Roald Amundsen - Hanssen, Helmer (Aschehoug, 1941)
Keywords: Antarktis; Fram (skip); Maud; Roald Amundsen; biografi; ekspedisjoner; oppdagelsesreiser; polarområdene; sledehunder; sydpolen

Oppdeling av polatraktene - Hoel, Adolf (Norge i Ishavet, 1941)
Keywords: Bouvetøya; Dronning Maud Land; Peter I. Øy; internasjonal politikk; polarområdene

Det Norske Geografiske Selskap (The Geographical Journal, 1939)
Keywords: Antarktis; Det Norske Geografiske Selskap; ekspedisjoner; geografi; polarområdene

Pelagic whaling in the Antarctic : 8 : The season 1937-1938 - Bergersen, Birger; Lie, J; Ruud, Johan T (I kommisjon hos Dybwad, 1939)
Keywords: Sørishavet; hvaler; hvalfangst; pelagisk; polarområdene

Pelagic whaling in the Antarctic : 7 : The season 1936-1937 - Hjort, Johan; Lie, J; Ruud, Johan T; Ottestad, Per (I kommisjon hos Dybwad, 1938)
Inneholder: A preliminary report on: Variations in the size distribution of Southern blue and fin whales by Per Ottestad
Keywords: Sørishavet; hvaler; hvalfangst; pelagisk; polarområdene

Pelagic whaling in the Antarctic : 6 : The season 1935-1936 - Hjort, Johan; Lie, J; Ruud, Johan T (I kommisjon hos Dybwad, 1937)
Keywords: Sørishavet; hvaler; hvalfangst; pelagisk; polarområdene

Mot Fremtidenn - Brøgger, Anton Wilhelm (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1936)
Keywords: Antarktis; Roald Amundsen; ekspedisjoner; polarområdene; sydpolen

Voyages of a modern Viking - Hanssen, Helmer (George Routledge & Sons, 1936)
Keywords: Antarktis; Fram (skip); Maud; Roald Amundsen; biografi; ekspedisjoner; oppdagelsesreiser; polarområdene; sledehunder; sydpolen

Pelagic whaling in the Antarctic : 5 : The season 1934-1935 - Hjort, Johan; Lie, J; Ruud, Johan T (I kommisjon hos Dybwad, 1935)
Keywords: Sørishavet; hvaler; hvalfangst; hvalfangstkonferanse; pelagisk; polarområdene

Carsten Borchgrevink - Hoel, Adolf (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1935)
Keywords: Antarktis; Carsten Borchgrevink; ekspedisjoner; oppdagelsesreiser; polarområdene

Pelagic whaling in the Antarctic : 4 : The season 1933-1934 - Hjort, Johan; Lie, J; Ruud, Johan T; Hansen, Hans Edvard (I kommisjon hos Dybwad, 1934)
Inneholder også: Limits of the pack-ice in the Antarctic in the area between 40° W and 110° E / by H.E. Hansen. S. 39-41, kart.
Keywords: Sørishavet; havis; hvaler; hvalfangst; pelagisk; polarområdene; sjøis

Norwegian Pelagic whaling in the Antarctic. 3 : The season 1932-1933 - Hjort, Johan; Lie, J; Ruud, Johan T (I kommisjon hos Dybwad, 1933)
Keywords: Sørishavet; hvaler; hvalfangere; hvalfangst; pelagisk; polarområdene

Norwegian Pelagic whaling in the Antarctic. 1 : Whaling grounds in 1929-1930 and 1930-1931 - Hjort, Johan; Lie, J; Ruud, Johan T (I kommisjon hos Dybwad, 1932)
Keywords: Sørishavet; hvaler; hvalfangere; hvalfangst; pelagisk; polarområdene

De l'acquisition de souveraineté sur les territoires polaires - Smedal, Gustav; Rokseth, Pierre (Librairie Arthur Rousseau, 1932)
Keywords: Antarktis; internasjonal; jus; polarområdene; politikk

Antarctic Circumnavigation by the "Norvegia" (Geographical Review, 1931)
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjonen; ekspedisjoner; forskning; geografi; polarområdene

Antarctic Research by the Norvegia Expeditions and Others - Holtedahl, Olaf (The Geographical Journal, 1931)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Odd I.; Sørishavet; ekspedisjonen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Antarctic regions - Smedal, Gustav; Meyer, Chr. (Acquisition of sovereignty over polar areas, 1931)
Keywords: Antarktis; internasjonal; polarområdene; politikk; rett

Geografisk kronikk - Haffner, Einar (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1930)
Keywords: Antarktis; ekspedisjoner; historie; polarforskning; polarområdene

Erhvervelse av statshøihet over polarområder - Smedal, Gustav (Gyldendal, 1930)
Keywords: Antarktis; internasjonal; jus; polarområdene; politikk

16 år med Roald Amundsen : fra pol til pol - Wisting, Oscar (Gyldendal, 1930)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; biografier; ekspedisjoner; oppdagelsesreiser; polarområdene

Antarctic whaling and exploration - Aagaard, Bjarne (Scottish Geographical Magazine, 1929)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Amundsen: Supreme Adventurer - Finley, John H (Geographical Review, 1929)
Keywords: Antarktis; Roald Amundsen; ekspedisjoner; forskning; polarområdene

Kaptein C.A. Larsen - Risting, Sigurd (Cappelen, 1929)
Keywords: Antarctic ekspedisjonen; Antarktis; Carl Anton Larsen; D/S Antarctic; D/S Jason; Jason ekspedisjonene; biografier; ekspedisjoner; erindringer; hvalfangere; hvalfangst; pelagisk; polarområdene; sjøfolk; sjømenn

Mitt liv som polarforsker - Amundsen, Roald (Gyldendal, 1927)
Keywords: Antarktis; biografi; ekspedisjoner; oppdagelsesreiser; polarområdene

My life as an explorer - Amundsen, Roald (Doubleday, Page, 1927)
Keywords: Antarktis; biografi; ekspedisjoner; oppdagelsesreiser; polarområdene

En helt : kaptein Scotts siste færd - Gran, Tryggve (Gyldendal, 1924)
Keywords: Antarktis; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; historie; oppdagelsesreiser; polarområdene; reiser

Hvor sydlyset flammer : leir- og ekspeditionsliv paa Antarktis : dagboksoptegnelser fra Scotts ekspedition - Gran, Tryggve (Gyldendal, 1915)
Keywords: Antarktis; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene; reiser

The Norwegian South Polar Expedition - Amundsen, Roald (Scottish Geographical Magazine, 1913)
Keywords: Antarktis; Fram (skip); Sydpolsekspedisjonen; ekspedisjoner; oppdagelsesreiser; polarområdene

The Norwegian South Polar Expedition - Amundsen, Roald (The Geographical Journal, 1913)
Keywords: Antarktis; Fram (skip); Sydpolsekspedisjonen; ekspedisjoner; geografi; oppdagelsesreiser; polarområdene

The Norwegian South Polar Expedition: Discussion - Shackleton, Ernest; Bruce, W S (The Geographical Journal, 1913)
Keywords: Antarktis; Sydpolsekspedisjonen; ekspedisjoner; oppdagelsesreiser; polarområdene

Amundsen`s Attainment of the South Pole (The National geographic magazine, 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Amundsen's Expedition to the South Pole (Bulletin of the American Geographical Society, 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Litt om vore ski, bindinger og fotbeklaedning samt deres betydning for sydpolsfaerden - Amundsen, Roald (Foreningen Til Ski-Idrettens Fremme. Årbok, 1912)
Keywords: Antarktis; ekspedisjoner; oppdagelsesreiser; polarområdene; ski; skisport; sydpolen

Sydpolen: den norske sydpolsfærd med Fram 1910-1912 - Amundsen, Roald (Jacob Dybwads forl., 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Sydpolen: den norske sydpolsfærd med Fram 1910-1912 - Amundsen, Roald (Jacob Dybwads forl., 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

The South Pole : an account of the Norwegian Antarctic expedition in the "Fram" 1910-1912 - Amundsen, Roald (Murray, 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

The South Pole : an account of the Norwegian Antarctic expedition in the "Fram" 1910-1912 - Amundsen, Roald (Murray, 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Amundsen`s Antarctic Explorations - Brown, R N Rudmose (Scottish Geographical Magazine, 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen